Current Federal Reserve Policy under the Lens of Economic History: A Review Essay - Williamson, Stephen D. (Journal of Economic Literature, 2016)
This review essay reviews the volume edited by Owen Humpage, Current Federal Reserve Policy under the Lens of Economic History: Essays to Commemorate the Federal Reserve System’s Centennial, and provides a broader perspective on central-banking issues. The papers in the Humpage volume address various aspects of central banking history, money, and private banking, with a focus on putting recent Fed policies in perspective. The topics covered include the role of the central bank as lender of last resort, the effects of open-market operations versus central-bank lending, central-bank independence, the political economy of monetary unions, financial crises, the effects of unconventional monetary policies, commodity monies, and the Canadian financial system as a natural experiment. (JEL E32, E52, E58, G01, G21, G28, N10)